Contribuições do PNAE na sustentabilidade dos agricultores familiares: o caso do município de Marechal Cândido Rondon - Constanty, Hadrien François Pierre-henri (2014)
This study contextualizes the Brazilian National School Feeding Program (PNAE) among other Brazilian public policies of family farming based on a sustainable development perspective. The case study is made up of two parts. In the first part the trajectory and the foundations of the policy are discussed, contextualized and analyzed from a theoretical view based on a literature search. The second part analyzes the practical implementation of the program and locally in the city of Marechal Cândido Rondon, in western Paraná state. The autonomy of the participants of the municipality program early 2013 is analyzed by an indicator of sustainability based on the logic of peasant agriculture. This case study was conducted through interviews of various actors involved in the municipality program between these farmers and local managers. Data were collected in the city hall in order to measure the progress and the scope of the program. Statistical analyzes were performed with the help of SPSS. The PNAE interacts more with civil society after 1994 when the program is decentralized, but it's actually from 2009, with the obligatory application of at least 30% of resources to family farming products, which PNAE plays a developmental role in supporting sustainability. In the city, PNAE responds on average for 13% of farmers incomes. The program promotes agroecological production because 50% of the municipal organic producers benefit from municipal PNAE. In addition, the program promotes agroecological practices by including family farms subsistence products in school meals. The case study reveals different degrees of autonomy that vary with the amount of available family labor and the importance of agricultural activities in incomes. The Program shows the way to a more sustainable development where the state can change the rules and correct the imperfection of a free market that grows negative externalities on social and environmental dimensions. State intervention in the market supports local production, keeping family farmers in the field and help the ecological conversion of farmers as well as reduce environmental impacts of the nacional program. Therefore, to put in perspective the billionary budget of the program, we should consider the limits of the program with regard to rural population. In Marechal Cândido Rondon, the data show that around 1% of the farmers deliver to the program. The data also confirm in practice the theory of the state in society where PNAE, like a public policy, is shaped by the social reality that interacts in its application both negatively as positively. We conclude that the PNAE strengthens the development of an inclusive economy, improving the income of family farmers but the expansion of the program should be considered within the local demand which is proportional to the population of the municipalities, and contradictorily favors urban municipalities